2012
DOI: 10.1088/1054-660x/23/2/025602
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity infrared lasers alter actin gene expression in skin and muscle tissue

Abstract: The biostimulative effect of low-intensity lasers is the basis for treatment of diseases in soft tissues. However, data about the influence of biostimulative lasers on gene expression are still scarce. The aim of this work was to evaluate the effects of low-intensity infrared lasers on the expression of actin mRNA in skin and muscle tissue. Skin and muscle tissue of Wistar rats was exposed to low-intensity infrared laser radiation at different fluences and frequencies. One and 24 hours after laser exposure, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
(41 reference statements)
2
9
0
Order By: Relevance
“…Also, red laser has no effect on XPA mRNA expression in burned skin [18]. In addition, laser-induced alteration on gene expression has been reported to alter the expression of other genes, as type 1 collagen [40], actin [19], myogenin and VEGF [41], Cox-2 [42], as well as mRNA from genes related to BER pathway of DNA repair [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, red laser has no effect on XPA mRNA expression in burned skin [18]. In addition, laser-induced alteration on gene expression has been reported to alter the expression of other genes, as type 1 collagen [40], actin [19], myogenin and VEGF [41], Cox-2 [42], as well as mRNA from genes related to BER pathway of DNA repair [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies comparing laser effects on mRNA expression from genes related to DNA lesion repair in different tissues. Previous data demonstrated that infrared laser exposure differently affects mRNA expression from genes coding enzymes involved in BER pathway of nuclear (APE1, OGG1, APEX1, and APEX2) [19,20,39] and mitochondrial (γ-polimerase) [20] DNA repair in skin and muscle tissue after infrared laser exposure. XPA and XPC mRNA expression is also differently altered in skin and muscle tissue after low-intensity infrared laser [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser exposure and zymosan-induced did cause neither DNA fragmentation nor cell death by caspase-6 pathway. Several studies have been reported controversial and possible adverse effects on cells and data about DNA damage after laser exposure in eukaryotic 42,43 and prokaryotic cells 32,[44][45] at different powers, wavelengths and fluences. In addition, as regard to DNA, a variety of studies have suggested that exposure to red and near infrared low-intensity lasers could induce adaptation or DNA damage at a sub-lethal level 32, 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Biological effects caused by free radicals from laser light are controversial and possible adverse effects on cells and data about DNA damage after laser exposure have been reported in eukaryotic [10][11][12][13][14] and prokaryotic cells [15][16][17][18][19][20][21][22][23] , at different powers, wavelengths and fluences. In addition, as regard to DNA, a variety of studies have suggested that exposure to red and near infrared low-intensity lasers could induce adaptation or DNA damage at a sub-lethal level.…”
Section: Introductionmentioning
confidence: 99%